2017
DOI: 10.1108/ajim-01-2017-0006
|View full text |Cite
|
Sign up to set email alerts
|

Recognition and reward in the academy

Abstract: Purpose-The publication oeuvre of a researcher carries great value when academic careers are assessed, and being recognised as a successful candidate is usually equated with being a productive author. Yet, how publications are valued in the context of evaluating careers is so far an understudied topic. The paper aims to discuss these issues. Design/methodology/approach-Through a content analysis of assessment reports in three disciplinesbiomedicine, economics and historythis paper analyses how externalities ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…A recent survey conducted in the UK found that academics tailor their publication practices to align with their institutional evaluation criteria 6. These criteria, however, may include metrics that are known to be problematic for assessing researchers 7. Current incentives and rewards may also be misaligned with the needs of society.…”
Section: Introductionmentioning
confidence: 99%
“…A recent survey conducted in the UK found that academics tailor their publication practices to align with their institutional evaluation criteria 6. These criteria, however, may include metrics that are known to be problematic for assessing researchers 7. Current incentives and rewards may also be misaligned with the needs of society.…”
Section: Introductionmentioning
confidence: 99%
“…Scholarly metrics, or bibliometrics, generally refers to the analysis of individual productivity and impact through publication and citation counts [1]. Broadly, methods of research performance and impact evaluation for the purposes of promotion, merit, and tenure have been offered that include the Hirsch Index (H-index), journal impact factor, number of publications, authorship position on publication, and citation rates [2][3][4]. Such metrics are used as "judgment devices" by reviewers and the scientific community in evaluation of an individual researcher and the impact of their work [4].…”
Section: Introductionmentioning
confidence: 99%
“…Similar arguments have led Crossik (2016) to emphasize the central position of the monograph in the culture and ecology in the humanities and most of the social sciences, and Bonaccorsi (2018) to state the books are the most important source in the SSH. Qualitative research by Hammarfelt (2017) illustrates the prestige of monographs in the field of history, and the commonness of book chapters in both history and economics. Similarly, Edwards (2012) argues that edited volumes allow for authoritative comparative perspectives across time, geographic localities and disciplinary borders.…”
Section: Research Processmentioning
confidence: 99%